2023
DOI: 10.1021/acs.macromol.2c02081
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polymer Brushes and Removable Surface Nanostructures on Tannic Acid Coatings

Abstract: Polymer brushes refer to polymer chains that are end-grafted to surfaces or interfaces at high grafting density. Polymer brushes are able to make surface self-assembly or surface coassembly with free block copolymer (BCP) chains, and surface nanostructures with different morphologies are formed on the surfaces. The formation of the surface nanostructures endows materials with new surface properties. To develop a simple and versatile approach to the synthesis of polymer brushes and surface nanostructures, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The results indicated that the Ag NPs’ specific surface area of TA 5 -PFRN@Ag catalyst is 2.82 times that of the PFRN@Ag catalyst. In addition, the abundant phenolic–OH groups on the TA coating can adsorbed the hydrophilic/benzene rings-containing reactions via H-bonding and π–π interactions. Meanwhile, the easily ionized phenolic–OH groups can make the surface of TA-PFRN@Ag catalysts show negative charges (−31.3 mV), and then the reactants can be adsorbed to the around of Ag NPs via electrostatic adsorption. Hence, the presence of TA layer makes the nanocomposites possess more adsorption sites for reactants on their Ag NPs’ surface, thereby improving the catalytic efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the Ag NPs’ specific surface area of TA 5 -PFRN@Ag catalyst is 2.82 times that of the PFRN@Ag catalyst. In addition, the abundant phenolic–OH groups on the TA coating can adsorbed the hydrophilic/benzene rings-containing reactions via H-bonding and π–π interactions. Meanwhile, the easily ionized phenolic–OH groups can make the surface of TA-PFRN@Ag catalysts show negative charges (−31.3 mV), and then the reactants can be adsorbed to the around of Ag NPs via electrostatic adsorption. Hence, the presence of TA layer makes the nanocomposites possess more adsorption sites for reactants on their Ag NPs’ surface, thereby improving the catalytic efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…(b) Schematic illustrations for the preparation of TA coatings on the surfaces of silica particles and the fabrication of nanostructures by self-assembly of polymer brushes and “free” block copolymers. Reprinted with permission from ref . Copyright 2023 The American Chemical Society.…”
Section: Synthesis Of Polymer Brushesmentioning
confidence: 99%
“…Wang and co-workers reported a simple method for the synthesis of polymer brushes. 52 As shown in Figure 3b, tannic acid (TA) molecules were attached onto the surfaces of amino-modified silica particles via hydrogen bonding, and quaternized poly (2-(dimethylamino)ethyl methacrylate)-blockpolystyrene (qPDMAEMA-b-PS) BCP chains were immobilized on the particle surfaces through electrostatic interactions between qPDMAEMA-b-PS and TA coatings. Because the noncovalent bonds can be cleaved, the fabrication of the polymer brushes through specific interactions provides a method for the synthesis of cleavable polymer brushes.…”
Section: ■ Synthesis Of Polymer Brushesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it exhibits comparable tensile strength and modulus to polyethylene terephthalate (PET), its elongation at break is confined to less than 10% and the notched impact strength falls below 20 J m À1 , consequently limiting its range of applications. [21][22][23][24][25][26][27][28][29][30] Thus, it is necessary to enhance the toughness of PLA. Various flexible polymers are preferred to toughen PLA such as poly (butylene succinate) (PBS), poly (ε-caprolactone) (PCL), and poly (butylene adipate-co-terephthalate) (PBAT).…”
Section: Introductionmentioning
confidence: 99%